A preparation method of a flaky carbonyl iron / molybdenum disulfide composite wave absorbing material and corresponding materials

By using a composite preparation method of sheet-shaped iron carbonyl carbonyl and molybdenum disulfide nanomaterial in electromagnetic wave absorption materials, filling molybdenum disulfide with different mass fractions, the problem of uncontrollable electromagnetic wave absorption range in multiple frequency bands in the prior art is solved, and the comprehensive controllability and absorption performance of electromagnetic waves from X-band to L-band is achieved.

CN117750751BActive Publication Date: 2025-03-07HEFEI UNIV OF TECH

Patent Information

Application Number
CN202410073937.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-18
Publication Date
2025-03-07
Estimated Expiration
2044-01-18

AI Technical Summary

Technical Problem

The prior art is difficult to adjust parameters, so that the absorption range of electromagnetic wave absorbing materials can be controlled within multiple frequency bands.

Method used

The preparation method of sheet-shaped iron carbonyl carbonyl/molybdenum disulfide composite absorbing material is adopted. By filling the molybdenum disulfide nanomaterials with different mass fractions, the electromagnetic parameters and the position of the absorption peaks of the material are regulated, so as to achieve comprehensive controllability of electromagnetic waves from the X-band to the L-band.

Benefits of technology

The overall improvement of the electromagnetic wave absorption performance of the material is achieved, and the absorption range can be controlledly adjusted within a certain range, thereby adapting to the electromagnetic wave absorption needs of different frequency bands.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117750751B_ABST
    Figure CN117750751B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of wave absorbing materials, and to a preparation method of a flaky carbonyl iron / molybdenum disulfide composite wave absorbing material and corresponding materials, comprising: adding sodium dodecylbenzene sulfonate, sodium molybdate, and thiourea to an ethanol solution according to a ratio and stirring to obtain a precursor solution; placing the precursor solution in a reactor for hydrothermal reaction to obtain a hydrothermal reaction solution, centrifugally washing the hydrothermal reaction solution to obtain a hydrothermal reaction product, vacuum drying the obtained hydrothermal reaction product to obtain a molybdenum disulfide nanomaterial; mixing the molybdenum disulfide nanomaterial with flaky carbonyl iron according to a ratio and grinding to obtain a mixed powder, bonding the mixed powder to obtain a flaky carbonyl iron / molybdenum disulfide composite wave absorbing material. The preparation method of the flaky carbonyl iron / molybdenum disulfide composite wave absorbing material and the corresponding materials of the invention can prepare a wave absorbing material with excellent electromagnetic wave absorption performance and can meet the absorption requirements of different frequency bands.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of absorbing materials, and in particular to a preparation method of a flaky carbonyl iron / molybdenum disulfide composite absorbing material and corresponding materials. Background Art

[0002] In recent years, with the rapid development of communication technology, human society has entered the era of the Internet of Everything. Among them, smart device applications represented by gigahertz (GHz) frequencies are being woven into the fabric of our daily lives. However, while smart devices bring convenience to our daily lives, they also bring corresponding electromagnetic wave pollution. In order to solve the increasingly serious electromagnetic pollution problem, more and more researchers are committed to the research of electromagnetic wave absorption and have achieved excellent results.

[0003] Electromagnetic wave absorbing materials are functional materials that can dissipate the incident electromagnetic wave energy by converting it into heat or other forms of energy through electromagnetic loss. The performance of electromagnetic wave absorbing materials depends on good impedance matching and multiple loss mechanisms. Among them, good impedance matching allows electromagnetic waves to enter the absorber as much as possible and achieve minimal reflection on the surface; the synergistic effect of multiple loss mechanisms (dielectric loss and magnetic loss) can strongly attenuate the energy of electromagnetic waves. At present, the main research frequencies are concentrated in the L band (1-2GHz), S band (2-4GHz), C band (4-8GHz), X band (8-12.4GHz) and Ku band (12.4-18GHz). However, in many studies, researchers mostly focus on one of the frequency bands, and there is no progress on how to adjust the parameters to move the electromagnetic wave absorption range of the sample within the above multiple bands.

[0004] Therefore, how to provide a method for preparing absorbing materials, accurately control the electromagnetic parameters of the sample while improving the absorbing performance, and achieve controllability in absorbing electromagnetic waves in different frequency bands has become a technical problem that needs to be solved urgently. Summary of the invention

[0005] In view of this, in order to overcome the deficiencies of the prior art, the present invention provides a method for preparing a flaky carbonyl iron / molybdenum disulfide composite absorbing material and corresponding materials.

[0006] In one aspect, the present invention provides a method for preparing a flaky carbonyl iron / molybdenum disulfide composite absorbing material, comprising:

[0007] Step 1: Preparation of precursor solution

[0008] Sodium dodecylbenzenesulfonate, sodium molybdate and thiourea are added into an ethanol solution according to a ratio and stirred to obtain a precursor solution;

[0009] Step 2: Preparation of MoS2 Nanomaterials

[0010] placing a precursor solution in a reactor for hydrothermal reaction to obtain a hydrothermal reaction solution, centrifugally washing the hydrothermal reaction solution to obtain a hydrothermal reaction product, and vacuum drying the obtained hydrothermal reaction product to obtain a molybdenum disulfide nanomaterial;

[0011] Step 3: Preparation of flaky carbonyl iron / molybdenum disulfide composite absorbing material

[0012] Molybdenum disulfide nanomaterials and flaky carbonyl iron are mixed according to a ratio and then ground to obtain mixed powders, which are then bonded to obtain flaky carbonyl iron / molybdenum disulfide composite wave absorbing materials.

[0013] Preferably, the preparation method of the flaky carbonyl iron / molybdenum disulfide composite absorbing material of the present invention, in step one, sodium dodecylbenzene sulfonate, sodium molybdate, and thiourea are added to an ethanol solution according to a ratio and stirred to obtain a precursor solution, comprising: adding 0.1 mol of sodium dodecylbenzene sulfonate, 0.1 mol of sodium molybdate and 0.07 mol of thiourea to 120 ml of an ethanol solution with a volume fraction of 50% and stirring to obtain a precursor solution.

[0014] Preferably, in the method for preparing the flaky carbonyl iron / molybdenum disulfide composite absorbing material of the present invention, in step 1, the stirring temperature is 20° C., the stirring speed is 450 rpm, and the stirring time is 60 min.

[0015] Preferably, in the method for preparing the flaky carbonyl iron / molybdenum disulfide composite absorbing material of the present invention, in step 2, the temperature of the hydrothermal reaction is 200° C., and the time of the hydrothermal reaction is 24 hours.

[0016] Preferably, in the method for preparing the flaky carbonyl iron / molybdenum disulfide composite absorbing material of the present invention, in step 2, the hydrothermal reaction solution is centrifugally cleaned to obtain a hydrothermal reaction product, comprising: using deionized water and anhydrous ethanol to centrifugally clean the hydrothermal reaction solution in sequence to obtain a hydrothermal reaction product.

[0017] Preferably, in the method for preparing the flaky carbonyl iron / molybdenum disulfide composite absorbing material of the present invention, in step 2, the vacuum drying temperature is 60° C. and the vacuum drying time is 12 h.

[0018] Preferably, the preparation method of the flaky carbonyl iron / molybdenum disulfide composite absorbing material of the present invention, in step three, the molybdenum disulfide nanomaterial and the flaky carbonyl iron are mixed according to a ratio and then ground to obtain a mixed powder, and the mixed powder is bonded to obtain the flaky carbonyl iron / molybdenum disulfide composite absorbing material, comprising: mixing 70 parts by weight of flaky carbonyl iron with 2-10 parts by weight of molybdenum disulfide nanomaterial and then grinding to obtain a mixed powder, and bonding the mixed powder with paraffin to obtain a flaky carbonyl iron / molybdenum disulfide composite absorbing material with paraffin as the base.

[0019] Preferably, in the method for preparing the flaky carbonyl iron / molybdenum disulfide composite absorbing material of the present invention, in step three, the total amount of the molybdenum disulfide nanomaterial, the flaky carbonyl iron and the paraffin is 100 parts by weight.

[0020] Preferably, in the method for preparing the flaky carbonyl iron / molybdenum disulfide composite absorbing material of the present invention, in step three, the grinding treatment time is 1 hour, and the bonding treatment temperature is 80°C.

[0021] On the other hand, the present invention provides a sheet-like carbonyl iron / molybdenum disulfide composite absorbing material, and the sheet-like carbonyl iron / molybdenum disulfide composite absorbing material is prepared according to the above method.

[0022] The preparation method of the flaky carbonyl iron / molybdenum disulfide composite wave absorbing material and the corresponding material of the present invention have the following beneficial effects:

[0023] 1. By filling molybdenum disulfide with different mass fractions, the electromagnetic parameters and absorption peak positions of the material are moved, achieving comprehensive controllability of electromagnetic waves from X-band to L-band within a certain range.

[0024] 2. The spherical molybdenum disulfide nanomaterial prepared by the present invention has strong conductivity and can regulate the dielectric parameters of the composite absorbing material; the flaky carbonyl iron has high magnetic permeability and strong magnetic loss capacity, and the uniform mixing of the two is conducive to coordinating the magnetoelectric coupling system and improving the overall electromagnetic wave absorption performance of the sample.

[0025] 3. The method of preparing flaky carbonyl iron / molybdenum disulfide composite absorbing material of the present invention has the characteristics of simple process, safety, reliability and pollution-free, and is suitable for large-scale production and promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 This is a SEM morphology of a flaky carbonyl iron / molybdenum disulfide composite absorbing material with a molybdenum disulfide filling amount of 2 wt % prepared in Example 1 of the present invention;

[0028] Figure 2 This is a SEM morphology of a sheet-like carbonyl iron / molybdenum disulfide composite absorbing material with a molybdenum disulfide filling amount of 4 wt % prepared in Example 2 of the present invention;

[0029] Figure 3 This is a SEM morphology of a flaky carbonyl iron / molybdenum disulfide composite absorbing material with a molybdenum disulfide filling amount of 6 wt % prepared in Example 3 of the present invention;

[0030] Figure 4 This is a SEM morphology of a sheet-like carbonyl iron / molybdenum disulfide composite absorbing material with a molybdenum disulfide filling amount of 8 wt % prepared in Example 4 of the present invention;

[0031] Figure 5 This is a SEM morphology of a flaky carbonyl iron / molybdenum disulfide composite absorbing material with a molybdenum disulfide filling amount of 10 wt % prepared in Example 5 of the present invention;

[0032] Figure 6 A reflection loss curve of a sheet-like carbonyl iron / molybdenum disulfide composite absorbing material with a molybdenum disulfide filling amount of 2 wt % prepared in Example 1 of the present invention at a thickness of 2.37 mm;

[0033] Figure 7 A reflection loss curve of a sheet-like carbonyl iron / molybdenum disulfide composite absorbing material with a molybdenum disulfide filling amount of 4 wt % prepared in Example 2 of the present invention at a thickness of 2.65 mm;

[0034] Figure 8 A reflection loss curve of a sheet-like carbonyl iron / molybdenum disulfide composite absorbing material with a molybdenum disulfide filling amount of 6 wt % prepared in Example 3 of the present invention at a thickness of 3.09 mm;

[0035] Fig. 9 A reflection loss curve of a sheet-like carbonyl iron / molybdenum disulfide composite absorbing material with a molybdenum disulfide filling amount of 8 wt % prepared in Example 4 of the present invention at a thickness of 4.50 mm;

[0036] Fig.10 This is a reflection loss curve of the sheet-like carbonyl iron / molybdenum disulfide composite absorbing material with a molybdenum disulfide filling amount of 10 wt% prepared in Example 5 of the present invention when the thickness is 5.00 mm. DETAILED DESCRIPTION

[0037] The embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0038] It should be noted that the following embodiments and features in the embodiments may be combined with each other in the absence of conflict; and, based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in the field without making any creative work are within the scope of protection of the present disclosure.

[0039] It should be noted that various aspects of the embodiments within the scope of the appended claims are described below. It should be apparent that the aspects described herein may be embodied in a wide variety of forms, and any specific structure and / or function described herein is merely illustrative. Based on the present disclosure, it should be understood by those skilled in the art that an aspect described herein may be implemented independently of any other aspect, and two or more of these aspects may be combined in various ways. For example, any number of aspects described herein may be used to implement the device and / or practice the method. In addition, other structures and / or functionalities other than one or more of the aspects described herein may be used to implement this device and / or practice this method.

[0040] Example 1

[0041] Preparation of flake carbonyl iron / molybdenum disulfide composite absorbing material:

[0042] Step 1: Preparation of precursor solution

[0043] 0.1 mol of sodium dodecylbenzene sulfonate, 0.1 mol of sodium molybdate and 0.07 mol of thiourea were added to 120 ml of 50% ethanol solution and stirred at 20° C., at a speed of 450 rpm and for 60 min to obtain a precursor solution;

[0044] Step 2: Preparation of MoS2 Nanomaterials

[0045] The precursor solution is placed in a reactor for a hydrothermal reaction at a temperature of 200° C. for 24 hours to obtain a hydrothermal reaction solution, and the hydrothermal reaction solution is centrifugally cleaned with deionized water and anhydrous ethanol in sequence to obtain a hydrothermal reaction product, and the obtained hydrothermal reaction product is vacuum dried at a temperature of 60° C. for 12 hours to obtain a molybdenum disulfide nanomaterial;

[0046] Step 3: Preparation of flaky carbonyl iron / molybdenum disulfide composite absorbing material

[0047] Molybdenum disulfide nanomaterials and flaky carbonyl iron are mixed according to a ratio and then ground to obtain mixed powders, which are then bonded to obtain flaky carbonyl iron / molybdenum disulfide composite wave absorbing materials.

[0048] 70 parts by weight of flaky carbonyl iron and 2 parts by weight of molybdenum disulfide nanomaterials were mixed and ground for 1 hour to obtain a mixed powder. The mixed powder was bonded with 28 parts by weight of paraffin at a temperature of 80°C to obtain a paraffin-based flaky carbonyl iron / molybdenum disulfide composite absorbing material.

[0049] Example 2

[0050] Preparation of flake carbonyl iron / molybdenum disulfide composite absorbing material:

[0051] Step 1: Preparation of precursor solution

[0052] 0.1 mol of sodium dodecylbenzene sulfonate, 0.1 mol of sodium molybdate and 0.07 mol of thiourea were added to 120 ml of 50% ethanol solution and stirred at 20° C., at a speed of 450 rpm and for 60 min to obtain a precursor solution;

[0053] Step 2: Preparation of MoS2 Nanomaterials

[0054] The precursor solution is placed in a reactor for a hydrothermal reaction at a temperature of 200° C. for 24 hours to obtain a hydrothermal reaction solution, and the hydrothermal reaction solution is centrifugally cleaned with deionized water and anhydrous ethanol in sequence to obtain a hydrothermal reaction product, and the obtained hydrothermal reaction product is vacuum dried at a temperature of 60° C. for 12 hours to obtain a molybdenum disulfide nanomaterial;

[0055] Step 3: Preparation of flaky carbonyl iron / molybdenum disulfide composite absorbing material

[0056] Molybdenum disulfide nanomaterials and flaky carbonyl iron are mixed according to a ratio and then ground to obtain mixed powders, which are then bonded to obtain flaky carbonyl iron / molybdenum disulfide composite wave absorbing materials.

[0057] 70 parts by weight of flaky carbonyl iron and 4 parts by weight of molybdenum disulfide nanomaterials were mixed and ground for 1 hour to obtain a mixed powder. The mixed powder was bonded with 26 parts by weight of paraffin at a temperature of 80°C to obtain a paraffin-based flaky carbonyl iron / molybdenum disulfide composite absorbing material.

[0058] Example 3

[0059] Preparation of flake carbonyl iron / molybdenum disulfide composite absorbing material:

[0060] Step 1: Preparation of precursor solution

[0061] 0.1 mol of sodium dodecylbenzene sulfonate, 0.1 mol of sodium molybdate and 0.07 mol of thiourea were added to 120 ml of 50% ethanol solution and stirred at 20° C., at a speed of 450 rpm and for 60 min to obtain a precursor solution;

[0062] Step 2: Preparation of MoS2 Nanomaterials

[0063] The precursor solution is placed in a reactor for a hydrothermal reaction at a temperature of 200° C. for 24 hours to obtain a hydrothermal reaction solution, and the hydrothermal reaction solution is centrifugally cleaned with deionized water and anhydrous ethanol in sequence to obtain a hydrothermal reaction product, and the obtained hydrothermal reaction product is vacuum dried at a temperature of 60° C. for 12 hours to obtain a molybdenum disulfide nanomaterial;

[0064] Step 3: Preparation of flaky carbonyl iron / molybdenum disulfide composite absorbing material

[0065] Molybdenum disulfide nanomaterials and flaky carbonyl iron are mixed according to a ratio and then ground to obtain mixed powders, which are then bonded to obtain flaky carbonyl iron / molybdenum disulfide composite wave absorbing materials.

[0066] 70 parts by weight of flaky carbonyl iron and 6 parts by weight of molybdenum disulfide nanomaterial are mixed and ground for 1 hour to obtain a mixed powder. The mixed powder is bonded with 24 parts by weight of paraffin at a bonding temperature of 80°C to obtain a paraffin-based flaky carbonyl iron / molybdenum disulfide composite absorbing material.

[0067] Example 4

[0068] Preparation of flake carbonyl iron / molybdenum disulfide composite absorbing material:

[0069] Step 1: Preparation of precursor solution

[0070] 0.1 mol of sodium dodecylbenzene sulfonate, 0.1 mol of sodium molybdate and 0.07 mol of thiourea were added to 120 ml of 50% ethanol solution and stirred at 20° C., at a speed of 450 rpm and for 60 min to obtain a precursor solution;

[0071] Step 2: Preparation of MoS2 Nanomaterials

[0072] The precursor solution is placed in a reactor for a hydrothermal reaction at a temperature of 200° C. for 24 hours to obtain a hydrothermal reaction solution, and the hydrothermal reaction solution is centrifugally cleaned with deionized water and anhydrous ethanol in sequence to obtain a hydrothermal reaction product, and the obtained hydrothermal reaction product is vacuum dried at a temperature of 60° C. for 12 hours to obtain a molybdenum disulfide nanomaterial;

[0073] Step 3: Preparation of flaky carbonyl iron / molybdenum disulfide composite absorbing material

[0074] Molybdenum disulfide nanomaterials and flaky carbonyl iron are mixed according to a ratio and then ground to obtain mixed powders, which are then bonded to obtain flaky carbonyl iron / molybdenum disulfide composite wave absorbing materials.

[0075] 70 parts by weight of flaky carbonyl iron and 8 parts by weight of molybdenum disulfide nanomaterials were mixed and ground for 1 hour to obtain a mixed powder. The mixed powder was bonded with 22 parts by weight of paraffin at a temperature of 80°C to obtain a paraffin-based flaky carbonyl iron / molybdenum disulfide composite absorbing material.

[0076] Example 5

[0077] Preparation of flake carbonyl iron / molybdenum disulfide composite absorbing material:

[0078] Step 1: Preparation of precursor solution

[0079] 0.1 mol of sodium dodecylbenzene sulfonate, 0.1 mol of sodium molybdate and 0.07 mol of thiourea were added to 120 ml of 50% ethanol solution and stirred at 20° C., at a speed of 450 rpm and for 60 min to obtain a precursor solution;

[0080] Step 2: Preparation of MoS2 Nanomaterials

[0081] The precursor solution is placed in a reactor for a hydrothermal reaction at a temperature of 200° C. for 24 hours to obtain a hydrothermal reaction solution, and the hydrothermal reaction solution is centrifugally cleaned with deionized water and anhydrous ethanol in sequence to obtain a hydrothermal reaction product, and the obtained hydrothermal reaction product is vacuum dried at a temperature of 60° C. for 12 hours to obtain a molybdenum disulfide nanomaterial;

[0082] Step 3: Preparation of flaky carbonyl iron / molybdenum disulfide composite absorbing material

[0083] Molybdenum disulfide nanomaterials and flaky carbonyl iron are mixed according to a ratio and then ground to obtain mixed powders, which are then bonded to obtain flaky carbonyl iron / molybdenum disulfide composite wave absorbing materials.

[0084] 70 parts by weight of flaky carbonyl iron and 10 parts by weight of molybdenum disulfide nanomaterials were mixed and ground for 1 hour to obtain a mixed powder. The mixed powder was bonded with 20 parts by weight of paraffin at a temperature of 80°C to obtain a paraffin-based flaky carbonyl iron / molybdenum disulfide composite absorbing material.

[0085] Example 6

[0086] The microscopic morphology of the flaky carbonyl iron / molybdenum disulfide composite absorbing materials prepared in Example 1, Example 2 and Example 3 was observed using a cold field emission scanning electron microscope of model Hitachi S4800. The acceleration voltage used was 5 kV. The SEM morphology images of the flaky carbonyl iron / molybdenum disulfide composite absorbing materials prepared in Example 1, Example 2, Example 3, Example 4 and Example 5 are shown in Table 1. Figure 1 , Figure 2 , Figure 3 , Figure 4 and Figure 5 .

[0087] Figure 1 This is a SEM morphology of a flaky carbonyl iron / molybdenum disulfide composite absorbing material with a molybdenum disulfide filling amount of 2 wt % prepared in Example 1 of the present invention; Figure 2 This is a SEM morphology of a sheet-like carbonyl iron / molybdenum disulfide composite absorbing material with a molybdenum disulfide filling amount of 4 wt % prepared in Example 2 of the present invention; Figure 3 This is a SEM morphology of a flaky carbonyl iron / molybdenum disulfide composite absorbing material with a molybdenum disulfide filling amount of 6 wt % prepared in Example 3 of the present invention; Figure 4 This is a SEM morphology of a sheet-like carbonyl iron / molybdenum disulfide composite absorbing material with a molybdenum disulfide filling amount of 8 wt % prepared in Example 4 of the present invention; Figure 5 This is a SEM morphology of a sheet-like carbonyl iron / molybdenum disulfide composite absorbing material with a molybdenum disulfide filling amount of 10 wt % prepared in Example 5 of the present invention; Figure 1-5 As shown, the SEM morphology of the flaky carbonyl iron / molybdenum disulfide composite absorbing materials prepared in Examples 1 to 5 is composed of flaky carbonyl iron and spherical molybdenum disulfide, wherein the flaky carbonyl iron is 1.5-7 μm long, 1-5 μm wide, and has a smooth surface; the diameter of the spherical molybdenum disulfide is about 3-5 μm.

[0088] The dielectric parameters of the sheet-like carbonyl iron / molybdenum disulfide composite absorbing materials prepared in Example 1, Example 2, Example 3, Example 4 and Example 5 were tested using a vector network analyzer of model N5230C PNA-L to obtain reflection loss curves. Figure 6-10 .

[0089] Figure 6 The reflection loss curve of the sheet-like carbonyl iron / molybdenum disulfide composite absorbing material with a molybdenum disulfide filling amount of 2 wt% prepared in Example 1 of the present invention at a thickness of 2.37 mm is shown; Figure 6 It can be seen that the reflection loss of the flaky carbonyl iron / molybdenum disulfide composite absorber is -57.59 dB, the effective absorption bandwidth (RL≤-10 dB) is 3.3 GHz, and its absorption range is in the C band (4-8 GHz).

[0090] Figure 7 The reflection loss curve of the sheet-like carbonyl iron / molybdenum disulfide composite absorbing material with a molybdenum disulfide filling amount of 4 wt% prepared in Example 2 of the present invention at a thickness of 2.65 mm is shown; Figure 7 It can be seen that the reflection loss of the flaky carbonyl iron / molybdenum disulfide composite absorber is -55.53dB, its center frequency is 4.74GHz, and the effective absorption bandwidth (RL≤-10dB) is 2.5GHz. This is because molybdenum disulfide itself has excellent conductive properties and makes a certain contribution to the adjustment of dielectric parameters.

[0091] Figure 8 The reflection loss curve of the sheet-like carbonyl iron / molybdenum disulfide composite absorbing material with a molybdenum disulfide filling amount of 6 wt% prepared in Example 3 of the present invention at a thickness of 3.09 mm is shown; Figure 8 It can be seen that the reflection loss of the flaky carbonyl iron / molybdenum disulfide composite absorber is -54.86dB, its center frequency is 3.68GHz, and the effective absorption bandwidth (RL≤-10dB) is 1.8GHz. This is because MoS2 provides conductive loss and FCIP provides magnetic loss, which makes the flaky carbonyl iron / molybdenum disulfide composite absorber have excellent absorbing performance.

[0092] Fig. 9 The reflection loss curve of the sheet-like carbonyl iron / molybdenum disulfide composite absorbing material with a molybdenum disulfide filling amount of 8 wt% prepared in Example 4 of the present invention at a thickness of 4.50 mm is shown; Fig. 9 It can be seen that the reflection loss of the flaky carbonyl iron / molybdenum disulfide composite absorber is -25.65dB, its center frequency is 2.0GHz, and the effective absorption bandwidth (RL≤-10dB) is 0.9GHz.

[0093] Fig.10The reflection loss curve of the sheet-like carbonyl iron / molybdenum disulfide composite absorbing material with a molybdenum disulfide filling amount of 10 wt% prepared in Example 5 of the present invention at a thickness of 5.00 mm is shown; Fig.10 It can be seen that the reflection loss of the flaky carbonyl iron / molybdenum disulfide composite absorber is -7.32dB, its center frequency is 1.21GHz, and its absorption range is in the L band (1-2GHz).

[0094] The preparation method of the flaky carbonyl iron / molybdenum disulfide composite wave absorbing material and the corresponding material of the present invention have the following beneficial effects:

[0095] 1. By filling molybdenum disulfide with different mass fractions, the electromagnetic parameters and absorption peak positions of the material are moved, achieving comprehensive controllability of electromagnetic waves from X-band to L-band within a certain range.

[0096] 2. The spherical molybdenum disulfide nanomaterial prepared by the present invention has strong conductivity and can regulate the dielectric parameters of the composite absorbing material; the flaky carbonyl iron has high magnetic permeability and strong magnetic loss capacity, and the uniform mixing of the two is conducive to coordinating the magnetoelectric coupling system and improving the overall electromagnetic wave absorption performance of the sample.

[0097] 3. The method of preparing flaky carbonyl iron / molybdenum disulfide composite absorbing material of the present invention has the characteristics of simple process, safety, reliability and pollution-free, and is suitable for large-scale production and promotion.

[0098] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.

Claims

1. A method for preparing a flaky carbonyl iron / molybdenum disulfide composite absorbing material, characterized in that: The method comprises: Step 1: Preparation of precursor solution Sodium dodecylbenzenesulfonate, sodium molybdate and thiourea are added into an ethanol solution according to a ratio and stirred to obtain a precursor solution; Step 2: Preparation of MoS2 Nanomaterials placing a precursor solution in a reactor for hydrothermal reaction to obtain a hydrothermal reaction solution, centrifugally washing the hydrothermal reaction solution to obtain a hydrothermal reaction product, and vacuum drying the obtained hydrothermal reaction product to obtain a molybdenum disulfide nanomaterial; Step 3: Preparation of flaky carbonyl iron / molybdenum disulfide composite absorbing material Molybdenum disulfide nanomaterials and flaky carbonyl iron are mixed according to a ratio and then ground to obtain a mixed powder, and the mixed powder is bonded to obtain a flaky carbonyl iron / molybdenum disulfide composite absorbing material; In step 1, sodium dodecylbenzene sulfonate, sodium molybdate, and thiourea are added to an ethanol solution according to a ratio and stirred to obtain a precursor solution, including: adding 0.1 mol of sodium dodecylbenzene sulfonate, 0.1 mol of sodium molybdate, and 0.07 mol of thiourea to 120 ml of an ethanol solution with a volume fraction of 50% and stirring to obtain a precursor solution; In step three, the molybdenum disulfide nanomaterial and the flaky carbonyl iron are mixed according to a ratio and then ground to obtain a mixed powder, and the mixed powder is bonded to obtain a flaky carbonyl iron / molybdenum disulfide composite absorbing material, including: 70 parts by weight of flaky carbonyl iron and 2-10 parts by weight of molybdenum disulfide nanomaterial are mixed and then ground to obtain a mixed powder, and the mixed powder is bonded with paraffin to obtain a flaky carbonyl iron / molybdenum disulfide composite absorbing material based on paraffin; In step 3, the total amount of the molybdenum disulfide nanomaterial, the flaky carbonyl iron and the paraffin is 100 parts by weight.

2. The method for preparing the flaky carbonyl iron / molybdenum disulfide composite absorbing material according to claim 1, characterized in that: In step 1, the stirring temperature is 20° C., the stirring speed is 450 rpm, and the stirring time is 60 min.

3. The method for preparing the flaky carbonyl iron / molybdenum disulfide composite absorbing material according to claim 1, characterized in that: In step 2, the temperature of the hydrothermal reaction is 200° C., and the time of the hydrothermal reaction is 24 h.

4. The method for preparing the sheet-like carbonyl iron / molybdenum disulfide composite absorbing material according to claim 1, characterized in that: In step 2, the hydrothermal reaction solution is centrifugally cleaned to obtain a hydrothermal reaction product, including: using deionized water and anhydrous ethanol to centrifugally clean the hydrothermal reaction solution in sequence to obtain a hydrothermal reaction product.

5. The method for preparing the flaky carbonyl iron / molybdenum disulfide composite absorbing material according to claim 1, characterized in that: In step 2, the vacuum drying temperature is 60° C., and the vacuum drying time is 12 h.

6. The method for preparing the sheet-like carbonyl iron / molybdenum disulfide composite absorbing material according to claim 1, characterized in that: In step three, the grinding treatment time is 1 hour, and the bonding treatment temperature is 80°C.

7. A sheet-like carbonyl iron / molybdenum disulfide composite absorbing material, characterized in that: The material is prepared according to any one of claims 1-6.

Citation Information

Patent Citations

  • Molybdenum disulfide / carbonyl iron composite microwave absorbent with core-shell structure and preparation method of molybdenum disulfide / carbonyl iron composite microwave absorbent

    CN107286907A

Cited By

  • Heteroatom-oxide co-doped carbon layer coated flaky carbonyl iron as well as preparation method and application method thereof

    CN121494077A

  • Heteroatom-oxide co-doped carbon layer coated sheet-shaped carbonyl iron and preparation method and application method thereof

    CN121494077B